A study of 54 cases of cerebellar Astrocytoma (In paediatric age group) - AL-Shalchy, Ali K. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: cerebellar astrocytroma is the commonest paediatric posterior fossa tumor. Patients and method: 54 patients taken from the neuro-surgical unit in the specialized surgical hospital from Aug 1995 till March 2003, all patients studied thoroughly age, gender, Presentation, Radiological diagnoses, surgery, additive therapy & final outcome including 5 years survival & conclusion is reached. Results and discussion: the results show that more than half of the patients were at age 5-7 years with very slight male predominance, most cases diagnosed by CT, some with MRI or MRI alone.Surgery was done for all cases & 16 patients’ preceeded by VP shunt. The final out come is compared with other similar studies. Conclusion: cerebellar astrocytoma acommon post fossa pediatric tumor if diagnosed early & proper surgery is done early, good prognosis can be gained.